Trend Of Research Design On Teaching English As A Foreign Language - Afro' Desinta; Y. Gatot Sutapa Yuliana (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to describe the results of content analysis on the Trend Of Research Design On Teaching English As A Foreign Language for two years (2020-2022) on the Scopus index. The research design used is quantitative with content analysis of 42 search results manuscripts using publish or perish. The results of this study found that the research design trend of Teaching English As A Foreign Language was dominated by Qualitative n = 8 (19%) and Mix method n = 8 (19%). And the least is Quantitative case study and Qualitative content analysis n= 1 (2%). Thus, the author recommends for future research on Teaching English As A Foreign Language to further explore the design of quantitative case studies and qualitative content analysis. Whether as a research thesis, master thesis, and dissertation.